Diversity of Medicinal Plants on Coastal Forest in Tangkoko Natural Reserve - Diah Irawati Dwi Arini; Julianus Kinho (Jurnal Wasian, 2015)
The purpose of this research was to determine the potential diversity of medicinal plants in the coastal forests of Tangkoko Nature Reserve. The research was conducted in August and September 2009. The data were obtained through deep interviews with people who use herbs from the Tangkoko coastal forest. Field observations carried out to see what kind of herbs that are known by a list of medicinal plant species interviews. Data were analyzed descriptively and presented in tabular form or image. The results showed there are at least 45 species from Tangkoko coastal forest used in traditional medicine in community village of Batu Putih. Forty-five plant species were grouped into 31 Family which types of Family Euphorbiaceae had the highest number of species are 6 types. Based on habitus, known 25 species classified as trees, 10 species of shrubs, 7 types of herb and 3 types included in the vines. The several types of medical plants are often used consist of Epipremium elegans Engl used for injury., Ear inflammation using Canarium asperum Benth, thrush using Adenostema sp., kidney using Arenga pinata Wurmb Merr, or Callophyllum inophyllum L.), and herb for the treatment of postpartum (Eltingera rosea BLBurtt & RMSm.).